1987
DOI: 10.1073/pnas.84.8.2198
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP regulation of the human glycoprotein hormone alpha-subunit gene is mediated by an 18-base-pair element.

Abstract: ABSTRACTcAMP regulates transcription of the gene encoding the a-subunit of human chorionic gonadotropin (hCG) in choriocarcinoma cells (BeWo). To define the sequences required for regulation by cAMP, we inserted fragments from the 5' flanking region of the a-subunit gene into a test vector containing the simian virus 40 early promoter (devoid of its enhancer) linked to the bacterial chloramphenicol acetyltransferase (CAT) gene. Results from transient expression assays in BeWo cells indicated that a 1500-base-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
130
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(133 citation statements)
references
References 24 publications
3
130
0
Order By: Relevance
“…This effect on basal promoter activity of the aCG gene CRE was restricted to choriocarcinoma cells and required a tandem repeat of the CRE consensus sequence (6). In contrast, Silver et al (43) found no effect of the 18-bp repeat of the aCG gene on basal promoter activity of a different choriocarcinoma cell line but did observe significant stimulation when longer 5'-flanking sequences of the aCG gene were fused to the SV1 promoter in a CAT fusion gene.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This effect on basal promoter activity of the aCG gene CRE was restricted to choriocarcinoma cells and required a tandem repeat of the CRE consensus sequence (6). In contrast, Silver et al (43) found no effect of the 18-bp repeat of the aCG gene on basal promoter activity of a different choriocarcinoma cell line but did observe significant stimulation when longer 5'-flanking sequences of the aCG gene were fused to the SV1 promoter in a CAT fusion gene.…”
Section: Discussionmentioning
confidence: 92%
“…The CREs of PEPCK and other genes have the properties of enhancers; they act in a relatively distance-and orientation-independent manner on their own promoters as well as on heterologous promoters (5,6,33,43,44). However, the core consensus sequence of the somatostatin gene was shown to be insufficient for mediation of cAMP responses (33), which indicates that additional sequence is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear, however, that flanking sequence can play an important role in influencing the level of activation and tissue specificity. The actual size of the CRE/ATF sites can vary a great deal in the number of bases required for proper activity (10,32,38,40). Our observations that part of the NF-KB-like site is protected from Exo III digestion and that mutation of the NF-KB-like site results in an increase in induction of the IL-13-CAT construct in U937 cells may mean that the actual CRE/ATF-like site includes the NF-KB-like site.…”
Section: Resultsmentioning
confidence: 99%
“…Recently the CAMP-responsive DNA elements of several genes, including rat phosphoenolpyruvate carboxykinase [22], somatostatin [23], human proenkephalin [24] and chorionic gonadotropin genes [25], have been reported to have some homologous sequence in common. Reverse genetic analysis of the bovine P-450(C21) gene, another steroidogenic P-450 gene, has been performed with Y-1 adrenal cells to clarify a regulatory region of the gene expression by Parker et al [26].…”
Section: Determination Of the Transcription Initiation Sitementioning
confidence: 99%